Dimensional Assessment of Anxiety in Puerto Rican Patients: Evaluating Applicability of Psychological Questionnaires - González-Barrios, Polaris; Morales-Rodríguez, Carlos M.; Merced-Morales, Kritzianel; Lampón, Anabelle; González, Rafael; Martínez, Karen (Puerto Rico Health Sciences Journal, 2016)
Objective: A dimensional assessment model as a supplement to the diagnosis process could overcome the current pitfalls in classifying psychopathology in ethnic minorities. The aim of the study described herein was to examine a sample of Puerto Rican patients diagnosed with anxiety disorder in order to evaluate the psychometric properties of the specific scales that assess the following 3 domains: clinical symptoms, personality/trait, and affective style. Methods: 80 subjects were recruited and interviewed using the Structured Clinical Interview for DSM-IV to identify the presence of anxiety disorders. Following this, various questionnaires assessing each proposed domain were administered to the participants. Reliability and validity of these questionnaires were examined using Cronbach’s alpha and exploratory factor analysis. The effect of the individual items of the questionnaires on the overall reliability and validity was assessed using factor scores component matrix. Results: Analyses revealed moderate to high reliability and validity scores within all 3 domains. The sample obtained moderate to high scores on the scales comprising clinical and personality/trait domains. Conclusion: The use of self-report scales in accordance with the proposed dimensional framework may be an effective way to supplement categorical diagnoses within the Hispanic population represented by this sample.